Modified method for the determination of cobalt (II) and copper (II) ions by adopting schiff base complexes in water of Shatt Al-Arab river - Mohammed, M.H. (Mesopotamian Journal of Marine Sciences, 2022)
A new method of complex formation between cobalt or copper ions and Schiff Base (derived from Schiff Base of salicyldehyde and amino acids) was adopted for the determination of cobalt and copper ions in water samples of Shatt Al-Arab River. For water sampling three stations along Shatt Al-Arab River were selected as follows: 1) discharging point in Shatt Al-Arab from Basrah paper and mill industries, 2) Karmatt Ali Bridge, and 3) Siba downstream to the southern region of Shatt Al-Arab river. After the formation of a complex with Schiff Base, Cobalt and Copper in the water of Shatt Al-Arab were determined spectrophotometricaly at wave length of 270 nm and 295 nm respectively. It is found that cobalt concentrations were (0.152, 0.174, 0.165) mg.l-1 and copper concentrations were (0.014, 0.021, 0.023) mg.l-1 in stations 1, 2 and 3, respectively. The method is reliable with sensitivity, accuracy, standard deviation and detection limit of (0.0235 gm.cm.l-1, 3.05×10-6, 0.00184, 0.52×10-7) for cobalt complex and (0.0135 gm.cm.l-1, 3.31×10-6, 0.00215, 0.6×10-8) for copper complex, respectively.